PENINGKATAN PENJUALAN PUPUK ORGANIK PADA FORUM PERSATUAN PEMUDA KREATIF (FP2K) DESA SAMBELIA MELALUI PELATIHAN, MANAJEMEN USAHA DAN PROMOSI DIGITAL - Imtihan, Khairul; Mardi, Mardi; Bagye, Wire; Rodi, Muhamad (Universitas Mataram, 2024)
The Forum Persatuan Pemuda Kreatif (FP2K) of Sambelia District was initially established as a platform for discussion and talent exploration, as well as for carrying out social activities in the community. The forum consists of 32 members with diverse backgrounds in terms of education, profession, and age. Most of its members are young people who rely on the agriculture and livestock sectors. One of the main products produced by FP2K is organic fertilizer, with 95% of its raw materials sourced from goat manure, a resource that is very abundant in the region. However, despite producing organic fertilizer since 2016, its output has not yet been able to meet the needs of farmers in Sambelia Village, especially considering that the demand for chemical fertilizers from the industry is often insufficient and the prices are high. The purpose of this training is to increase knowledge and skills in organic fertilizer production, develop more effective fertilizer business management, utilize digital media as a promotional tool to expand the market, promote economic independence for the youth, and increase the sales and production of organic fertilizer to meet the needs of farmers in Sambelia Village. The training method in this community service activity includes several stages, namely socialization, training, technology implementation, mentoring, evaluation, and program sustainability. The training provided covers various topics, including the production and packaging of compost fertilizer, creating promotional video content using Canva, managing Facebook pages, YouTube, promotional content, and financial management using MS Excel. The results of the community service training have been well executed, with an average understanding rate for each training topic of 85.98, and the training activities were conducted smoothly, receiving positive feedback from participants, the Head of Sambelia Village, the District Head of Sambelia, and the surrounding community. The average pre-test results for each training topic were 54.4, and the post-test results showed an increase of 31.58, reaching 85.98.